Predicting of Psychological Distress Based on Stress Coping Styles, Attitude towards the Severity of Covid-19 and Preventive Behaviors in Corona Epidemics in the People of Isfahan - Hoeein Ali Mehrabi; Nasrin Afshari (Taḥqīqāt-i ̒Ulūm-i Raftārī, 2022)
Aim and Background: The coronavirus epidemic, a phenomenon that shocked the world with its emergence, began in December 2019 in Wuhan, China. Since then, the virus has spread around the world and to date, millions of people have been affected by the disease. This study aimed to predict psychological distress based on coping styles with stress, attitudes toward risk severity, and preventive behaviors of people in Isfahan in terms of corona disease. Methods and Materials: The research design was a descriptive correlational study. The statistical population of this study was all people over 18 years old living in Isfahan in 1400 that 351 of them were selected using the available sampling method, responded to questionnaires of Kessler psychological distress, Indler and Parker coping styles stressful situations (short form) and Corona Attitude and preventive measures made by Honarvar & et. al. The data were analyzed using statistical methods Pearson correlation and stepwise regression via SPSS 28. Findings The results of the analysis showed that attitude toward the severity of covid19, avoidant coping style, emotion-focused coping style, and preventive behaviors can Predict 18% of changes in psychological distress significantly. But Problem-focused coping styles could not predict psychological distress. Conclusions: The results of the present study can be used to formulate individualistic and community interventions to promote the health of people with epidemic diseases.